Contribuição ao conhecimento taxonômico dos Braconidae (Hymenoptera, Ichneumonoidea) do sudeste brasileiro, com ênfase na subfamília Alysiinae - Oliveira, Franciélle Dias de (Universidade Federal de São Carlos, 2021)
This study had as main objective to contribute to the taxonomic knowledge of Braconidae (Hymenoptera, Ichneumonoidea), with emphasis on the subfamily Alysiinae, of two protected areas (Unidades de Conservação) in the southeastern region of Brazil, namely: Parque Nacional da Serra da Canastra (São Roque de Minas, MG) and Parque Nacional da Serra dos Órgãos (Teresópolis, RJ). In the Parque Nacional da Serra da Canastra, the study was conducted in the upper part of the Park (at 1,180 to 1,444 m altitude), in gallery forest and rupestrian grassland (sensu stricto) areas, between November 2018 and December 2019, with the use of Moericke, Malaise and light traps. In this Park, more than 9,000 specimens of 24 subfamilies of Braconidae were sampled. The results obtained with Moericke traps suggested a positive association of the abundance and richness of subfamilies with the relative humidity of the air. The composition of subfamilies differed between the two phytophysiognomies sampled. The most abundant subfamilies were Doryctinae, Microgastrinae and Cheloninae. Cenocoelinae, Rhysipolinae, and Rhyssalinae had few specimens collected and were sampled exclusively in gallery forests; specimens of Miracinae occurred only in rupestrian grasslands. The Malaise trap was the most effective method for collecting specimens, however, the Moericke traps were important in relative abundance, especially for Alysiinae, Doryctinae and Pambolinae, and the only specimen of Rhysipolinae obtained was with the use of this method; with the light trap, a high diversity of subfamilies was sampled. Seven known genera (and two undescribed genera), 63 morphospecies and 223 specimens of Alysiinae were sampled in this Park, predominantly from gallery forests, but specimens of Coelinius occurred only in rupestrian grasslands. The composition of morphospecies differed between the sampled phytophysiognomies and the sample sufficiency was not achieved for any of the three methods used. In the Parque Nacional da Serra dos Órgãos, collections were carried between December 2014 and November 2015, in an altitudinal gradient at 137 to 2,140 m. Twelve known genera (and two undescribed genera) of Alysiinae were obtained in this Park and about 2,900 specimens. Above 860 m of altitude, 90% of the specimens were sampled; a positive association between abundance and the average altitude of the sample area was found. In contrast, specimens of Orthostigma were obtained only in areas at 350 m. Considering the two protected areas, 14 known genera of Alysiinae and two undescribed genera were sampled. The most abundant genera were Dinotrema, Aspilota and Aphaereta. Relatively rare and/or little recorded genera in the Neotropical Region occurred (Alysia, Idiasta, Coelinius, Ilatha, Rhacalysia, and Orthostigma). This research provided support for an update of the genera Idiasta and Rhacalysia, including the description of new species from the Neotropical Region.
Contribution to the taxonomic knowledge of the Braconidae (Hymenoptera, Ichneumonoidea) of brazilian southeast, with emphasis on the subfamily Alysiinae
Keywords: Vespa parasitoide; Taxonomia; Ecologia; Campo rupestre; Mata atlântica; Altitude; Gradiente altitudinal; Região neotropical; Parasitoid wasp; Taxonomy; Ecology; Rupestrian grassland; Atlantic forest; Altitude; Altitudinal gradient; Neotropical region; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES